Hyalocytes in proliferative vitreo-retinal diseases. (4th July 2022) - Jones, Charlotte H.; Gui, Wei; Schumann, Ricarda G.; Boneva, Stefaniya K.; Lange, Clemens A. K.; van Overdam, Koen A.; Chui, Toco Y. P.; Rosen, Richard B.; Engelbert, Michael; Sebag, J.
ABSTRACT: Introduction: Hyalocytes are sentinel macrophages residing within the posterior vitreous cortex anterior to the retinal inner limiting membrane (ILM). Following anomalous PVD and vitreoschisis, hyalocytes contribute to paucicellular (vitreo-macular traction syndrome, macular holes) and hypercellular (macular pucker, proliferative vitreo-retinopathy, proliferative diabetic vitreo-retinopathy) diseases. Areas covered: Studies of human tissues employing dark-field, phase, and electron microscopies; immunohistochemistry; and in vivo imaging of human hyalocytes. Expert opinion: Hyalocytes are important in early pathophysiology, stimulating cell migration and proliferation, as well as subsequent membrane contraction and vitreo-retinal traction. Targeting hyalocytes early could mitigate advanced disease. Ultimately, eliminating the role of vitreous and hyalocytes may prevent proliferative vitreo-retinal diseases entirely.